2019
DOI: 10.1002/micr.30531
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative vascular mapping for anterolateral thigh flap surgeries: A clinical trial of photoacoustic tomography imaging

Abstract: Background Photoacoustic tomography (PAT) is a noninvasive vascular imaging modality that uses near‐infrared pulse laser beams and ultrasound (US) to visualize vessels. We previously demonstrated the utility of PAT for visualizing anterolateral thigh (ALT) perforators in a clinical study of 10 thighs in 5 healthy adults. Evaluation of the correlation between PAT and US findings showed that PAT had comparable diagnostic potential but was superior in visualizing subcutaneous microvessels; however, there was no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Additionally, they involve high costs, have a limited observation window, expose patients to radiation, and can fail to accurately visualize the perforasome of individual perforators due to their limited resolutions. Meanwhile, infrared thermography, which has been described previously by researchers (26), can automatically and reliably detect the perforators in thermograms, but the detailed information produced cannot be clearly visualize. Moreover, photoacoustic tomography, as a branch of photoacoustic image technology, was previously used to identify the location of the anterolateral thigh perforator in clinical study; however, due to its poor resolution and contrast, it is difficult to visualize very small perforators or the clear boundary of perforators, which can significantly limit the perforator flap design.…”
Section: Maxmentioning
confidence: 99%
“…Additionally, they involve high costs, have a limited observation window, expose patients to radiation, and can fail to accurately visualize the perforasome of individual perforators due to their limited resolutions. Meanwhile, infrared thermography, which has been described previously by researchers (26), can automatically and reliably detect the perforators in thermograms, but the detailed information produced cannot be clearly visualize. Moreover, photoacoustic tomography, as a branch of photoacoustic image technology, was previously used to identify the location of the anterolateral thigh perforator in clinical study; however, due to its poor resolution and contrast, it is difficult to visualize very small perforators or the clear boundary of perforators, which can significantly limit the perforator flap design.…”
Section: Maxmentioning
confidence: 99%
“…Photoacoustic tomography (PAT) is a 3-dimensional (3D) vascular mapping technology that has recently been used in preoperative planning for flap harvest [16,17] . This technology uses energy from a near infrared pulse laser which is absorbed by hemoglobin.…”
Section: Photoacoustic Tomographymentioning
confidence: 99%
“…This technology can be particularly useful in the harvest of perforator based ALT free flaps due to its ability to map the supra-fascial course of the vessels. Tsuge et al [16] showed PAT is comparable to ultrasound in the evaluation of supra-fascial perforator branching patterns and is better than ultrasound at showing oblique and horizontally oriented branches. This can be particularly useful in the process of thinning ALT flaps to expand its utility in defects requiring a thin flap [18] .…”
Section: Photoacoustic Tomographymentioning
confidence: 99%
See 2 more Smart Citations